Extensive Gingival Enlargement in Siblings: A case report - Pushpanshu, Kumar (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2012)
Gingival fibromatosis is characterised by varying degrees of fibrotic gingival overgrowth that can be caused by a variety of aetiological factors. Hereditary gingival fibromatosis (HGF) is a rare genetic disorder, characterised by a slowly progressive, benign enlargement of keratinised gingiva. The condition may be found in an autosomal dominant or autosomal recessive mode of inheritance, the former being more common. It usually develops as an isolated disorder but can be one feature of a multisystem syndrome. Accordingly, HGF has been divided into two forms: non-syndromic and syndromic. The gingival enlargement can be localised or generalised, but usually involves both arches. The authors describe a case of non-syndromic generalised severe HGF, involving the maxillary and mandibular arches in two brothers. This report focuses on the diagnosis, treatment, and control of the disease. The pattern of inheritance and histopathologic characteristics are also emphasised.